A prisoner of one's own mind: Identifying and understanding existential isolation. (15th January 2017) - Pinel, Elizabeth C.; Long, Anson E.; Murdoch, Erin Q.; Helm, Peter
Abstract: Although often treated as a singular construct, social isolation can assume an interpersonal or an existential form (Yalom, 1980 ). Here we develop an individual difference measure of existential isolation, or, isolation with regard to one's experience of reality (Pinel, Long, Landau, & Pyszczynski, 2004; Yalom, 1980 ). We detail the validation of the Existential Isolation Scale and provide evidence of its convergent, discriminant, and criterion validities (Studies 1 and 2). In addition, we show that levels of existential isolation remain stable over a two-week period (Study 3), but also change as expected among those primed with the construct (Study 3). In the discussion, we review research that further establishes the uniqueness of this construct and its relevance to understanding the causes and consequences associated with social isolation more broadly construed. Highlights: We introduce the Existential Isolation Scale (EIS). A CFA confirms the one-facture structure of the EIS. The EIS is distinct from scores on measures of interpersonal isolation. Scores on the EIS remain stable over a 2-week period. A situational manipulation of existential isolation increased scores on the EIS.